Decoupled extensional faulting and forced folding in the southern part of the Roer Valley Graben, Belgium. (December 2015) - Deckers, Jef
Abstract: During late Oligocene incipient rifting, the southern part of the Roer Valley Graben was characterized by normal faulting and forced folding of its Paleogene pre-rift strata. The 2D seismic data used in this study shows that these faults and forced folds were geometrically decoupled from faults or fault zones in the underlying Triassic and older strata. Geometric decoupling consistently took place in an interval that comprises (latest Triassic to Early Jurassic) soft claystones on top of (Triassic) alternations of evaporites and claystones layers. This mechanically weak interval probably inhibited the upward propagation of (re)activated underlying faults, resulting in the formation of the observed forced folds (monoclines) in the overlying Paleogene pre-rift strata. Strain from the sub-detachment faults was distributed along the mechanically weak interval towards detachment edges, leading to the consistent presence of faults in the footwall domain of the supra-detachment monoclines. The mechanically weak interval was thereby able to maintain the kinematic coherency between geometrically decoupled under- and overlying deformation throughout late Oligocene rifting. Highlights: During late Oligocene incipient rifting in the Roer Valley Graben, extensional deformation was locally geometrically decoupled. The interval that triggered decoupling consists of Triassic to Lower Jurassic incompetent claystones and evaporite layers. Underneath the incompetent interval, extension was accommodated by faulting in the Triassic and older strata. On top of the incompetent interval, extension was accommodated by faults and forced folds in the Paleogene pre-rift strata. The incompetent interval was able to maintain the kinematic coherency between the geometrically decoupled deformation.